2019
DOI: 10.1007/s10064-018-01451-5
|View full text |Cite
|
Sign up to set email alerts
|

Minding the geotechnical data gap: appraisal of the variability of key soil parameters for slope stability modelling in Saint Lucia

Abstract: Identification of failure thresholds and critical uncertainties associated with slope stability often requires the specification of geotechnical parameter values for input into a physically-based model. The variation of these parameters (including mechanical soil properties such as effective friction angle and cohesion) can have a significant impact on the computed factor of safety. These uncertainties arise from natural variations in soils, measurement techniques, and lack of reliable information. Researchers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…Compilation of geodatabases can help reduce geotechnical uncertainty for design and assessment (cf. Ching and Phoon, 2014;Kulhawy and Mayne, 1990;Roopnarine et al, 2012;Shepheard et al, 2019). A key study Piya (2004) compiled a database of 185 well logs and 328 shallow boreholes to produce a single knowledge base of geological information for the Kathmandu Valley.…”
Section: Geodatabasesmentioning
confidence: 99%
“…Compilation of geodatabases can help reduce geotechnical uncertainty for design and assessment (cf. Ching and Phoon, 2014;Kulhawy and Mayne, 1990;Roopnarine et al, 2012;Shepheard et al, 2019). A key study Piya (2004) compiled a database of 185 well logs and 328 shallow boreholes to produce a single knowledge base of geological information for the Kathmandu Valley.…”
Section: Geodatabasesmentioning
confidence: 99%
“…Physical models may involve different geotechnical factors, which may help these models generate forecasts about slope failures (Tofani et al, 2017;Bicocchi et al, 2019). However, physical models involving different geotechnical factors may be constraint by the underlying mechanics explaining slope failures (Yalcin 2011;Igwe, 2015;Tofani et al, 2017;Bicocchi et al, 2019;Shepheard et al, 2019). Amidst constraints in physical models, data-driven machine-learning (ML) techniques may provide an alternate approach for predicting slope failures (Aloetti and Chowdhury 1999; Kavzoglu et al, 2014;Huang et al, 2017;Park et al, 2019;Asheghi et al, 2020;Moayedi et al, 2021).…”
Section: Saint Lucia Statistical Methodsmentioning
confidence: 99%
“…Statistical methods Porosity, dry density, angle of internal friction, and saturated permeability Shepheard et al (2019)…”
Section: Italymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Shepheard et al (2019) have shown in that Weibull distribution may better describe peak effective friction angle (φ'peak) (number of datapoints (n) = 85) and cohesion intercept (c') (n = 86) for a database of soils from the island of Saint Lucia.…”
Section: Probability Distributions In Geotechnical Engineeringmentioning
confidence: 99%